The Low Density Matter (LDM) beamline at FERMI: optical layout and first commissioning. (20th April 2015) - Svetina, Cristian; Grazioli, Cesare; Mahne, Nicola; Raimondi, Lorenzo; Fava, Claudio; Zangrando, Marco; Gerusina, Simone; Alagia, Michele; Avaldi, Lorenzo; Cautero, Giuseppe; de Simone, Monica; Devetta, Michele; et al.
<x xml:space="preserve">Abstract</x> The Low Density Matter (LDM) beamline has been built as part of the FERMI free‐electron laser (FEL) facility to serve the atomic, molecular and cluster physics community. After the commissioning phase, it received the first external users at the end of 2012. The design and characterization of the LDM photon transport system is described, detailing the optical components of the beamline.